Peran Perguruan Tinggi Negeri Berbadan Hukum (PTN-BH) terhadap Kinerja Kependidikan Islam - Riana Sari Sitorus; Ahmad Raihan; Ahmad Darlis; Indah Rizka Rahmi (Journal on Education, 2023)
Education is very important in human life, because with education humans can develop and advance their potential to become human beings who have the ability to face various challenges in all areas of life, so to make this happen it is necessary to make improvements to the national education system. The term Legal Entity State University is first mentioned in Article 65 paragraph 1 of Law Number 12 of 2012, where it is stated that "The implementation of Higher Education autonomy can be given selectively based on performance evaluation by the Minister to PTN by applying the Public Service Agency Financial Management Pattern or by establishing PTN Legal Entities to produce quality Higher Education”. The purpose of this study is the role of Legal Entity State Universities (PTN-BH) on the performance of Islamic education. This study uses a qualitative method. Qualitative research is research that presents data with descriptions. Data collection technique is done by observation method. This type of research is field research. Data analysis consists of three components, namely data reduction, data presentation and conclusion.